2006
DOI: 10.1142/s0192415x06004272
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Clinical Effects of Physical Therapy and Acupuncture to Treat Spontaneous Frozen Shoulder

Abstract: The integration of traditional Chinese and Western medicine and their clinical effects have been widely evaluated. Many studies have shown that using a combination of these two remedies has resulted in better outcomes than using only one of them. Acupuncture is a traditional Chinese medical technique, which plays an important role in enforcing pain control, prevention and functional improvement. In 1979, the World Health Organization (WHO) journal introduced acupuncture as a remedy for 43 diseases, including f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 10 publications
0
51
0
2
Order By: Relevance
“…A summary of study characteristics is reported in 80 and two three-armed trials. 79,81 Sample sizes ranged from 74 to 360.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…A summary of study characteristics is reported in 80 and two three-armed trials. 79,81 Sample sizes ranged from 74 to 360.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study used acupuncture 81 and two studies used electroacupuncture, 79,80 The number of acupuncture points needled ranged from three to five. Although needle point prescriptions varied between studies, two studies both included Hegu (LI4) and Jianyu (LI15) needle points.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations